Electroreduction of nitrogen at almost 100 percent current-to-ammonia efficiency - Du, H. L.; Chatti, M.; Hodgetts, R. Y.; Cherepanov, P. V.; Nguyen, C. K.; Matuszek, K.; Simonov, A. N.
Beyond its use in the fertiliser and chemical industries1, ammonia is currently seen as a potential replacement for carbon-based fuels and as a carrier for worldwide transportation of renewable energy2. Implementation of this vision requires transformation of the existing fossil fuel based technology for NH3 production3 to a simpler, scale-flexible technology, such as the electrochemical lithium-mediated nitrogen reduction reaction (Li-NRR)3,4. This provides a genuine pathway from N2 to ammonia, yet is hampered by limited yield rates and efficiencies4-12. Here we investigate the role of the electrolyte in this reaction and present a high-efficiency, robust process enabled by compact ionic layering in the electrode-electrolyte interfacial region. The interface is generated by a high-concentration imide-based lithium salt electrolyte, enabling stabilised ammonia yield rates of 150±20 nmol s-1 cm-2 and current-to-ammonia efficiency closely approaching 100 percent. The ionic assembly formed at the electrode surface suppresses electrolyte decomposition and supports stable N2 reduction. Our study highlights the interrelation between the performance of the Li-NRR and the physicochemical properties of the electrode-electrolyte interface. We anticipate that these findings will guide the development of a robust, high-performance process for sustainable ammonia production.